Diagenetic alteration, pore structure, and reservoir quality of the tight sandstone reservoirs in the Lishu fault depression in the Songliao Basin, northeastern China - Zhu Jianfeng; Pang Haiming; Li Zhongbo (Energy Exploration & Exploitation, 2025)
The analytical approaches including thin-section petrography, X-ray diffraction, scanning electron microscopy energy dispersive spectrometer, and high-pressure mercury intrusion porosimetry were conducted on the sandstone reservoirs in the Lishu fault depression to investigate the diagenetic alteration and their impacts on pore structure and reservoir quality. The results show that correlations between diagenetic processes and reservoir properties are observed. Six diagenetic facies, namely the strong compaction with moderate cementation facies (SCMCF), weak dissolution with cementation facies (WDCF), moderate cementation with feldspar dissolution facies (MCFDF), moderate cementation with residual intergranular pore facies (MCRIPF), moderate cementation with fracture facies (MCFF), and moderate cementation with mixed dissolution facies (MCMDF), were classified through detailed examination of microscopic petrography. Variations in pore volumes, pore size distribution, and pore fractal dimensions, alongside their influencing factors, were analyzed to elucidate the impacts of diagenetic processes on the reservoir quality of tight sandstones. The diagenetic coefficient and mineral composition are considered critical determinants of pore structure. Specifically, SCMCF and WDCF are regarded as unfavorable diagenetic facies. MCFDF and MCRIPF are categorized as moderate diagenetic facies. Conversely, MCFF and MCMDF are considered favorable diagenetic facies. The SCMCF and WDCF suggest a relatively low heterogeneity, Conversely, the MCFDF, MCRIPF, MCFF, and MCMDF show obvious reservoir heterogeneity and low pore-throat connectivity. The fractal properties of the WDCF, MCFDF, MCRIPF, and MCMDF are obvious, indicating relatively complex pore structures. This article provides insights into the relationships among the diagenetic facies, pore structure, fractal dimension, and reservoir quality of tight sandstones in the Lishu fault depression, in addition, has significance for the reservoir evaluation and exploration of tight sandstone gas the rift Basins.